IMPACT OF HIGH PERFORMANCE WORK PRACTICES (HPWP) ON EMPLOYEE RETENTION IN IT INDUSTRY - Kumar, Dr. D. Pradeep; Sreekanth, Mr. B.; Dr. S. Mohana, (The journal of contemporary issues in business and government, 2022)
This research article aims to “ To study the impact of key attributes of HR practices on employee retention of IT employees” . The paper applies data reduction using Reliability Test, Confirmatory Factor Analysis (CFA) and Multiple Linear Regression on a sample of 270 respondents drawn from 6 IT companies in Pune and condenses a set of 24 items of key HR practices converted into six attributes. The present study proposes a model of the impact of key attributes of HR practices on the employee retention. The study found that recruitment & selection, training & development, performance appraisal, retaining talent, employee feedback and work-life-balance are impacting significantly the employee retention. Therefore, IT companies should focus on the above factors to increase retention of employees. The study investigated the impact of attributes of HR practices on the retention of the IT employees concluded that performance appraisal had the highest impact on the retention of the employees’ recruitment &selection, training & development, retaining talent, employee feedback followed by work-life-balance.